Networks beyond Empires : Chinese Business and Nationalism in the Hong Kong-Singapore Corridor, 1914-1941. - Kuo, Huei-Ying (Chinese overseas., 2014)
In Networks beyond Empires, Kuo finds that Chinese speech-group ties were key to understanding diasporic businesses and nationalism. These transnational networks transformed the Hong Kong-Singapore corridor into a space autonomous from Chinese official nationalism and British as well as Japanese empires.